Gene profiling and characterization of arginine kinase-1 (MrAK-1) from freshwater giant prawn (Macrobrachium rosenbergii) - Arockiaraj, J.; Vanaraja, P.; Easwvaran, S.; Singh, A.; Alinejaid, T.; Othman, R.Y.; Bhassu, S. (Academic Press, 2011)
Arginine kinase-1 (MrAK-1) was sequenced from the freshwater prawn Macrobrachium rosenbergii using Illumina Solexa Genome Analyzer Technique. MrAK-1 consisted of 1068 bp nucleotide encoded 355 polypeptide with an estimated molecular mass of 40 kDa. MrAK-1 sequence contains a potential ATP:guanido phosphotransferases active domain site. The deduced amino acid sequence of MrAK-1 was compared with other 7 homologous arginine kinase (AK) and showed the highest identity (96%) with AK-1 from cherry shrimp Neocaridina denticulate. The qRT-PCR analysis revealed a broad expression of MrAK-1 with the highest expression in the muscle and the lowest in the eyestalk. The expression of MrAK-1 after challenge with the infectious hypodermal and hematopoietic necrosis virus (IHHNV) was tested in muscle. In addition, MrAK-1 was expressed in Escherichia coli by prokaryotic expression plasmid pMAL-c2x. The optimum temperature (30 °C) and pH (8.5) was determined for the enzyme activity assay. MrAK-1 showed significant (P < 0.05) activity towards 10-50 mM ATP concentration. The enzyme activity was inhibited by α-ketoglutarate, glucose and ATP at the concentration of 10, 50 and 100 mM respectively. Conclusively, the findings of this study indicated that MrAK-1 might play an important role in the coupling of energy production and utilization and the immune response in shrimps.